Communication and Economic Life: by Liz Moor (Cambridge, UK: Polity, 2022). Issue 2 (3rd April 2023) - Sherman, Zoe
Abstract : Liz Moor's Communication and Economic Life analyzes the overlaps between communicative practices and economic actions. Economic actions can convey information and can carry a symbolic dimension. Communication practices—that is, promotion, information, narrative, and discussion—shape how people understand themselves as economic actors and also the actions they take. Moor's analysis is particularly compelling when power inequalities come to the foreground, as in her treatment of asymmetries in data mining and her treatment of how the contemporary employment system compels workers to engage in self-promoting communication.